2020
DOI: 10.1186/s12889-020-09675-5
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic and demographic factors determining the underweight prevalence among children under-five in Punjab

Abstract: Background Underweight prevalence continues to be major public health challenge worldwide, particularly in developing countries like Pakistan. This study is focused on socio-economic and demographic aspects of underweight prevalence among children under-five in Punjab. Methods In this study, several socioeconomic and demographic factors are considered using MICS-4 data-set. Only those variables which are usually described in the nutritional studies of children were picked. Covariates include: the age of child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…As such, a significant negative association is observed between the two variables, suggesting that women who are exposed to media learn about the diet and health of their children and allocating even the limited income to devote to the health nutrition of their children. This finding is consistent with previous research evidence reported in other countries [ 9 , 70 , 75 , 77 , 78 ]. Further, the CIAF status was negatively associated with the DHS year in Ethiopia.…”
Section: Discussionsupporting
confidence: 94%
“…As such, a significant negative association is observed between the two variables, suggesting that women who are exposed to media learn about the diet and health of their children and allocating even the limited income to devote to the health nutrition of their children. This finding is consistent with previous research evidence reported in other countries [ 9 , 70 , 75 , 77 , 78 ]. Further, the CIAF status was negatively associated with the DHS year in Ethiopia.…”
Section: Discussionsupporting
confidence: 94%
“…Similarly, lower socioeconomic backgrounds were linked to a heightened likelihood of underweight among school adolescents, in line with findings from Farooq et al [24] and Galgamuwa et al [25], emphasizing the importance of addressing socioeconomic inequalities in combating underweight across diverse educational settings. However, no significant association was found between nutritional knowledge and underweight, despite adolescents' generally satisfactory nutritional knowledge and predominantly normal nutritional status.…”
Section: Discussionsupporting
confidence: 83%
“…The incidence of underweight is also observed to be associated with the BMI of mother ( p < 0.000) and the education of father ( p < 0.002). Both the predictors have a direct bearing on underweight children (Nahar et al, 2010 ; Biswas & Bose, 2011 ; Meshram et al, 2012b ; Cesare et al, 2015 ; Agu et al, 2019 ; Farooq et al, 2020 ). There are two important predictors observed to be statistically significant in models 1 and 2 for CIAF of children as it is highly determined by the BMI of mother ( p < 0.000), which is well recorded by earlier research works (Ansuya et al, 2018 ; Wong et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%